C-CoP hollow microporous nanocages based on phosphating regulation: a high-performance bifunctional electrocatalyst for overall water splitting. Issue 36 (11th September 2019) - Li, Wanping; Cheng, Gao; Sun, Ming; Wu, Zhaoxuan; Liu, Guanliang; Su, Dangsheng; Lan, Bang; Mai, Shixin; Chen, Liya; Yu, Lin
Abstract : Clever phosphating adjustment and rich conductive C coating collectively contribute to impressive water splitting performance of C-CoP-1/12. Abstract : Developing economic, effective and stable bifunctional electrocatalysts to achieve sustainable hydrogen production is highly desired. Herein, C-coated CoP hollow microporous nanocages (C-CoP-1/12) are synthesized by calcination of a Prussian blue analog precursor and subsequent phosphorization treatment. Under alkaline condition, the C-CoP-1/12 exhibit splendid electrocatalytic performance with a low overpotential of 173 mV for hydrogen evolution reaction (HER) and 333 mV for oxygen evolution reaction (OER) at a current density of 10 mA cm −2 . The C-CoP-1/12 show high electrocatalytic performance for overall water splitting at a low potential of only 1.650 V for the driving current density of 10 mA cm −2, and they exhibit remarkable stability for at least 24 h. The engineering of phosphating is the critical step for the synthesis of pure-phase CoP with hollow nanoarchitecture. Compared with Co2 P, CoP possesses lower water dissociation barrier and favorable Δ G H* value according to theoretical calculations, resulting in superior electrocatalytic performance. Such impressive water splitting performance is mainly attributed to the collective effects of metal phosphide with unique electronic structure, the shortened electron transport paths, and the conductive C coating. This strategy is believed to provide a basis for the development of electrode materials with highly efficient electrocatalytic water-splitting capability.